KAIN IDUP PANAK: OPTIMALISASI NILAI SEBAGAI INSPIRASI PENGEMBANGAN CULTURAL TOURISM DI DESA ADAT TENGANAN PEGRINGSINGAN - I Gusti Ngurah Agung Panji Tresna; I Putu Gede Eka Praptika (UHN IGB Sugriwa Denpasar, 2022)
The Tenganan Pegringsingan Traditional Village has a wide variety of traditions and cultures, both in the immaterial and material cultures form, which have become an attraction for Cultural Tourism. On the other hand, there is a cultural attraction in the form of works of art that are not widely known and optimized by cultural tourism stakeholders. This work of art is known as Idup Panak Woven. This study aims to explore the philosophical values implied in the Idup Panak Woven as an inspiration to optimize the development of Cultural Tourism. This research is a qualitative form of research and data collection techniques with observations, interviews, and literature studies based on Cultural Tourism theory as an analytical perspective. Then, the analysis's results show that Idup Panak Woven has three philosophical values, namely Beauty, Truth, and Kindness. These values correlated with the essences of Cultural Tourism, such as aesthetic, intellectual, and emotional. As a result, all of these philosophical values can inspire the development of Cultural Tourism in the Tenganan Pegringsingan Traditional Village throughout the archipelago